Ash-flow sheets of early Miocene and early Pliocene age are present in the Castillo de Callalli, Arequipa Department, southern Perú - Noble, Donald C. (2003)
Two ash-flow sheets of markedly different age and petrography are exposed in the Castillo de Callalli. The lower, phenocryst-rich ash-flow sheet of low-silica rhyolite has a K-Ar age of 20.7 -+ 0.6 Ma. The overlying ash-flow sheet is composed of sanidine-bearing high-silica rhyolite. An 40Ar/39Ar age of 4.72 +- 0.02 Ma and petrographic characteristics show that the unit is almost certainly the lower ash-flow sheet of the Cailloma Tuff, which in adjacent quadrangles has been mapped variously as Fm. Sencca, Fm. Garza, Fm. Yauri, and Ignimbrita Acopata.